Mapping the Evolution of Sustainable Capitalism: A Bibliometric Analysis of Scholarly Trends and Influential Works - Shridhi Jain; Shubham Singhania; Varda Sardana; Amiya Kumar Mohapatra (Organizations and Markets in Emerging Economies)
The need to address global concerns has led to an increase in the significance of sustainable capitalism, which is located at the intersection of economics, business, and environmental studies. This study aims to delve into the theoretic evolution and academic structure of the relationship between sustainability and capitalism, by employing a bibliometric analysis. Relying on 687 documents, sourced from the Scopus database, this paper provides a thorough overview of the evolution of sustainable capitalism, highlighting significant turning points, essential themes, and new research directions. VOS-Viewer and R-Studio were used for implementing the techniques of citation, co-citation, and keyword analysis. The findings from the study have implications for multiple stakeholders. While the analysis could help researchers have a better understanding of the field and explore future research agendas, it can push the corporate houses to take necessary remedial actions for their past capitalist behavior. The study will also be beneficial for developing countries to understand the pressing issue of environmental damage and come up with cheaper yet effective ways to implement circular models of the economy.